ISOLATION AND IDENTIFICATION OF ANTIFUNGAL (Candida albicans) COMPOUND FROM THE HULL OF DELIMA FRUITS (Punica granatum L.) - Purwantini, Indah; Wahyuono, Subagus (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
The hull of delima fruits (Punica granatum L.) are traditionally used to cure dysmenorhoe. Preliminary study indicated that extract of the hull was able to inhibit the growth of Candida albicans. Therefore this study was aimed to isolate and identify active compounds responsible for the activity from the hull of P. granatum. The study was initiated by extracting the powdered material with petroleum ether followed by methanol. Antifungal activity test (100 mg/ml) indicated that the petroleum ether extract was more active than the methanol extract (inhibition zone: 10.59 vs 6.92 mm). The pet. ether extract was triturated by n-hexane to give n-hexane insoluble and n-hexane soluble fractions. The latter that was active (inh. zone: 9.50 vs 0.00 mm) was fractionated by vacuum liquid colomn chromatography (vlc; SiO2, n-hexane with increasing amount of ethylacetate) to give 7 fractions (F1-F7). Fraction 2 (inh. zone: 9.05 mm) and 3 (11.05 mm) displayed antifungal activity, then F3 was subjected to contact bioautography to give 2 active compounds [Rf. 0.50 (major) and 0.10 (minor)]. Preparative tlc [SiO2 F-254 nm; nhexane: ethylasetate 4-1, developed 2x) of F3 was aimed to separate 2 active compounds. Due to limited amount of the minor compound, the MFC was applied only for the major compound (Rf. 0.50; 200 mg/ml). The structure identification was done by mean of spectroscopic methods (uv, ir, ms and nmr) to be a setrol type of compound having stigmastane skeleton, esterified by a long-chain fatty acid.Keywords: Punica granatum L., Candida albicans, active compound, terpenoid